Wzrastanie i rozwój dziewcząt z nadwagą i otyłością Growth and development of overweight and obese girls - Iwona Wronka; 0 0 (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: The pattern of development of obesity during childhood and adolescence is unclear, hindering preventive strategies. Aim of the study: The aim of this study was to investigate the differences in growth and tempo of maturation between overweight or obese and normal weight girls. Materials and methods: The data were obtained from 1008 schoolgirls aged 16-18 years for whom earlier data on weight and height were available. The height and body mass were measured and the BMI was calculated. Height and weight in early life were assessed by medical records review. Underweight, overweight and obesity were assessed using the international BMI cut points, defined by Cole et al. Results: Girls in higher BMI categories at 7 years had significantly higher values of BMI at 9, 14 and 16-18 years of age, however only 10% of them were also overweight or obese at youth. Overweight and obese girls tend to lose body weight after the puberty period, whereas normal weight children tend to gain body weight. Overweight and obese children were significantly taller than their peers at 7, 9 and 14 years. Those differences vanished after the puberty period. The rate of height gain between ages 7 and 16-18 years was lower in girls with higher BMI values at childhood. Girls, those who were overweight or obese at young age experience menarche at a younger age than normal weight girls. Conclusion: The obtained data show that overweight and obesity in childhood is associated with rapid tempo of growth and maturity.